Culture Conversion at 6 Months in Patients Receiving Delamanid-containing Regimens for the Treatment of Multidrug-resistant Tuberculosis. (2nd November 2019) - Seung, Kwonjune J; Khan, Palwasha; Franke, Molly F; Ahmed, Saman; Aiylchiev, Stalbek; Alam, Manzur; Putri, Fauziah Asnely; Bastard, Mathieu; Docteur, Wisny; Gottlieb, Gary; Hewison, Catherine; Islam, Shirajul; et al.
Abstract: Delamanid should be effective against highly resistant strains of Mycobacterium tuberculosis, but uptake has been slow globally. In the endTB (expand new drug markets for TB) Observational Study, which enrolled a large, heterogeneous cohorts of patients receiving delamanid as part of a multidrug regimen, 80% of participants experienced sputum culture conversion within 6 months. Clinical Trials Registration . NCT02754765.